A comparative analysis of the smart money effect in Malaysian Islamic and conventional equity funds - Marzuki, A; Worthington, AC (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2024)
This paper undertakes a comparative analysis of the smart money' effectwhereby investors are able to identify funds that subsequently perform wellamong Malaysian Islamic and conventional domestic equity funds. We find that Islamic equity fund investors are unable to identify funds that will outperform benchmarks in the future. However, these same investors have some ability in identifying poorly performing funds. The key implications are as follows. First, Islamic equity investors naively chasing recently highly performing funds only incidentally benefit from mutual fund momentum strategies. Second, fund managers may be able to benefit from a contrary dumb money' effect found among Islamic equity fund investors in that they appear most concerned with only very poor performance in determining the flow of funds. Finally, we find high search costs may be one reason why investors naively chase past better performing funds.